The trans-Pacific imagination : rethinking boundary, culture and society - Sakai, Naoki, 1946-; Yoo, Hyon Joo (World Scientific, 2012)
This anthology critically re-examines and re-articulates the discursive boundary that binds the region called East Asia in order to produce Trans-Pacific Studies. Recognizing that the creation of regional boundaries depends on a new configuration of both inter- and intra-national power relations and the ideological constructs that generate historical, ideological, and cultural effects, this volume proposes that the term "trans-Pacific" be mobilized to complicate the phrase "East Asian" as the boundary of academic discipline and socio-cultural discourse. The anthology also examines the historical conditions under which “East Asia” was constructed as an area and the trans-Pacific directives that nurtured the sense of nationality in each component nation of East Asia.